2019
DOI: 10.1038/s41535-019-0196-6
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of spin memory in a crystalline, insulating phase-change material

Abstract: The description of disorder-induced electron localization by Anderson over 60 years ago began a quest for novel phenomena emerging from electronic interactions in the presence of disorder. Even today, the interplay of interactions and disorder remains incompletely understood. This holds in particular for strongly disordered materials where charge transport depends on 'hopping' between localized sites. Here we report an unexpected spin sensitivity of the electrical conductivity at the transition from diffusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Direct measurements of glassy spin response in materials other than Sb 2 Te 3 are yet to be carried out; it is clear, however, that for spin memory the spin-lifetime τ s has to be much longer than the hopping time τ. We expect spin memory to be visible in a broader family of strong SOC materials; it has been reported in SnSb 2 Te 4 33 , where crystal (and defect) structure is different 34 . The electrical control of this spin-dependent transport can, in principle, be achieved through electrostatic gating 35 , and by locally modifying spin correlations using currently practiced doping techniques.…”
Section: Discussionmentioning
confidence: 69%
“…Direct measurements of glassy spin response in materials other than Sb 2 Te 3 are yet to be carried out; it is clear, however, that for spin memory the spin-lifetime τ s has to be much longer than the hopping time τ. We expect spin memory to be visible in a broader family of strong SOC materials; it has been reported in SnSb 2 Te 4 33 , where crystal (and defect) structure is different 34 . The electrical control of this spin-dependent transport can, in principle, be achieved through electrostatic gating 35 , and by locally modifying spin correlations using currently practiced doping techniques.…”
Section: Discussionmentioning
confidence: 69%
“…Anderson localization in vacancy‐rich compounds was already investigated by Cutler and Mott in 1969, who showed that in Ce 2 S 3 , the random distribution of vacancies creates a tail of localized states in the conduction band, and that addition of a small number of cerium atoms per formula unit leads to a small number of electrons in the tail of the band and, thus, to insulating behavior. [ 31 ] More recently, Anderson localization effects were observed in rocksalt‐like compounds chemically related to the abovementioned PCMs, including SnBi 2 Te 4 and SnSb 2 Te 4 thin films, [ 32,33 ] and also in GeTe nanowires. [ 34 ] In ref.…”
Section: Figurementioning
confidence: 99%
“…[ 34 ] In ref. [ 32 ] , an isotropic positive magnetoconductivity was observed in the hopping regime of conductivity in SnSb 2 Te 4 thin films. The magnetoconductivity was shown to increase with disorder, and was ascribed to the destruction of spin correlations and spin memory effects, i.e., spin‐dependent hopping probabilities.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Anisotropic magnetoconductance has been reported in 2D films [15] and quasi-1D wires [16] of Anderson insulating In 2 O 3-x samples consistent with quantuminterference mechanism, and by inference, demonstrating quantum coherence on scales that exceed the localization length of the system. On the other hand, there are systems where these quantum-effects, while clearly observ-able in the diffusive regime, vanished or became overwhelmed by another mechanism once the system crossed over to the insulating side [17]. It appears that in some materials a dephasing mechanism is turned on in their localized phase, possibly related to the appearance of local magnetic-moments associated with singly-occupied sites [18].…”
mentioning
confidence: 99%